Plurality in the time of Christianization: the conception of Christian identities in North Africa (200-450 AD) - Campos, Ludimila Caliman (Romanitas - Revista de Estudos Grecolatinos, 2017)
Review of: REBILLARD, É. Christians and their many identities in Late Antiquity, North Africa, 200-450 CE. London: Cornell University Press, 2017. 144 p.
Keywords: Late Antiquity; Christianization; North Africa